First clinical‐grade porcine kidney xenotransplant using a human decedent model. Issue 4 (20th January 2022) - Porrett, Paige M.; Orandi, Babak J.; Kumar, Vineeta; Houp, Julie; Anderson, Douglas; Cozette Killian, A.; Hauptfeld‐Dolejsek, Vera; Martin, Dominique E.; Macedon, Sara; Budd, Natalie; Stegner, Katherine L.; Dandro, Amy; et al.
Abstract : A radical solution is needed for the organ supply crisis, and the domestic pig is a promising organ source. In preparation for a clinical trial of xenotransplantation, we developed an in vivo pre‐clinical human model to test safety and feasibility tenets established in animal models. After performance of a novel, prospective compatible crossmatch, we performed bilateral native nephrectomies in a human brain‐dead decedent and subsequently transplanted two kidneys from a pig genetically engineered for human xenotransplantation. The decedent was hemodynamically stable through reperfusion, and vascular integrity was maintained despite the exposure of the xenografts to human blood pressure. No hyperacute rejection was observed, and the kidneys remained viable until termination 74 h later. No chimerism or transmission of porcine retroviruses was detected. Longitudinal biopsies revealed thrombotic microangiopathy that did not progress in severity, without evidence of cellular rejection or deposition of antibody or complement proteins. Although the xenografts produced variable amounts of urine, creatinine clearance did not recover. Whether renal recovery was impacted by the milieu of brain death and/or microvascular injury remains unknown. In summary, our study suggests that major barriers to human xenotransplantation have been surmounted and identifies where new knowledge is needed to optimize xenotransplantation outcomes in humans. Abstract : The authors report the development of an in vivo, pre‐clinical, human model to test safety and feasibility tenets and show that major barriers to human xenotransplantation have been surmounted. Kirk comments on page 1007 .